2017
DOI: 10.1038/s41598-017-07473-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormones Regulate Leptin Transcript Accumulation and Protein Secretion in 3T3-L1 Cells

Abstract: Leptin is an adipokine produced by fat cells that regulates food consumption and metabolic activity. Sexual dimorphism in leptin and fat stores have been observed in humans and rodents with females having more leptin and greater levels of subcutaneous fat than males. One potential mechanism leading to this dimorphism is steroid hormone regulated synthesis of transcripts encoding leptin. Identification of direct regulatory mechanisms is difficult in animals or primary adipocytes due to these intertwined dimorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 94 publications
(108 reference statements)
2
26
0
1
Order By: Relevance
“…Adipose tissue is a highly heterogeneous organ with cell-and depot-specific functions [35][36][37]. However, we chose 3T3-L1 differentiated adipocytes because they are a well-characterized and widely used cell line in metabolic, molecular, and endocrine studies, including studies on leptin expression levels [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is a highly heterogeneous organ with cell-and depot-specific functions [35][36][37]. However, we chose 3T3-L1 differentiated adipocytes because they are a well-characterized and widely used cell line in metabolic, molecular, and endocrine studies, including studies on leptin expression levels [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased levels of leptin in the blood of females were associated with the action of sex hormones. It has been demonstrated that testosterone reduces the concentration of leptin [35], and estrogen increases leptin production in vivo [36] and in vitro [37]. Perhaps the sex-specific insulin response to food intake is a common phenomenon for different species: Men also have significantly higher postprandial insulin levels compared to women [19].…”
Section: Discussionmentioning
confidence: 99%
“…Sex steroids, depending on dose, had either inhibitory or no effect on lep and lepr expression in primary as well as secondary lymphoid organs of both the sexes, except on lepr in head kidney where DHT had marked stimulatory effect in male and E 2 in female. Since the effect of sex steroids on lep and lepr expression remain unexplored in immune organs of vertebrates, we analysed our results in light of observations in other tissues of fishes 26,28,29 and mammals 41,[50][51][52][53][54] . Our findings on lep and lepr expression in immune organs of C. punctata are largely contrasting to a recent study in immature male Salmo salar in which testosterone is reported to increase lep expression in liver and pituitary while plasma level of leptin has been shown to remain unchanged in androgen-treated fish 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, male as well as female sex steroids have been demonstrated to downregulate the expression of lep and its receptor in hepatocytes of immature female Cynoglossus semilaevis 31 . Apart from fishes, direct role of sex steroids has been explored also in mammals where androgens and estrogen are shown to have differential effects, inhibitory, stimulatory or no effect, on leptin production from adipocytes 18,[52][53][54] . Surprisingly, in vitro study to demonstrate the effect of sex steroids on expression of leptin receptor is missing in mammals.…”
Section: Discussionmentioning
confidence: 99%